Anthropological enquiries into policy, debt, business and capitalism - Wood, Donald C. (Emerald Publishing Limited, 2020)
Volume 40 of Research in Economic Anthropology explores current issues in national and international policy, cost and debt, business and capitalism, and economic theory and behavior specifically pertaining to Brazil. The underlying theme running through the collection is the steady encroachment of neoliberalism into economic policy and practice, and the impact this has had on everyday ways of life. In Part I, Raja Swamy explores post-disaster relocation and livelihood issues in Nagapattinam, Tamil Nadu, India, Anthony Rausch and Junichiro Koji investigate Japan's Hometown Tax Donation Program, and Emma Gilberthorpe argues for development plans that incorporate indigenous people's needs and worldviews. In Part II, Vassily Pigounides empirically analyzes a revenue management system originating in France, Irene Sabaté Muriel looks at the moral economy of mortgage lending and economic reasoning during the housing bubble that rocked Spain when it burst in 2007, and Mathias Krabbe explores debt among US college students. In Part III, Ieva Snikersproge examines a French worker cooperative ice cream venture, Andres Gramajo quantitively measures the strength of capitalist thought among business owners in Latin America, and Michal Stein and John Vertovec explore individual action in the transitional economy in Havana's tourist-oriented dance instruction world. In Part IV, Sidney Greenfield theorizes on two coexisting but disjunct patterns of behavior in Brazil, which give rise to tension, corruption allegations, and public scandals, and Guilherme Falleiros analyzes the structural shifts between global capitalism and indigenous ways of life in the same country.
Includes index.
Print version record.
Keywords: Economic policy; Debt; Business; Capitalism; Business & Economics -- Economics -- General; Economics